Pengaruh Tangibility, Pertumbuhan Perusahaan, Resiko Bisnis dan Profitabilitas terhadap Kebijakan Hutang - Devi permata sari; Mia Angelina Setiawan (Universitas Negeri Padang, 2021)
The purpose of this study was to exame the effect of tangibility, growth, business risk and profitability to debt policy. This research includes causative research the population used in this study are our property and real estate companies listed on Indonesia stock exchange of period 2017-2019. The sampling technique used in this study was purposive sampling technique. There are 30 property and real estate companies that were used as research sample. The type of data used is secondary data obtained from the official website of the Indonesian stock exchange and the official website of each company. The analytical method used is quantititave methods. The result shower that tangibility and company growth did not have a significant effect but had a positive relationship to debt policy, and business risk does not have a significant effect on debt policy but has a negative relationship debt policy.